Is the Future of Coronary Arterial Revascularization a Hybrid Approach?: The Canadian Experience across three Centers. Issue 2 (March 2017) - Giambruno, Vincenzo; Hafiz, Ahmad; Fox, Stephanie A.; Jeanmart, Hugues; Cook, Richard C.; Khaliel, Feras H.; Teefy, Patrick; Sridhar, Kumar; Lavi, Shahar; Bagur, Rodrigo; Randhawa, Varinder K.; Iglesias, Ivan; et al.
Objective: Hybrid coronary revascularization offers and combines the advantages of both surgical and percutaneous revascularization and eliminates at the same time the disadvantages of both procedures. The objective of this study was to assess graft and stent patency at 6 months, rate of bleeding, intensive care unit and hospital stay, rate of reintervention, and long-term clinical follow-up. Methods: From March 2004 to November 2015, a total of 203 patients underwent robotic-assisted minimally invasive direct coronary artery bypass graft of the left internal thoracic artery to the left anterior descending artery and PCI of a non-left anterior descending vessel in a single or two stage, at three different centers. Patients underwent 6-month angiographic follow-up. The mean ± SD clinical follow-up was 77.82 ±41.4 months. Results: Successful hybrid coronary revascularization occurred in 196 of the 203 patients. One hundred forty-six patients underwent simultaneous surgical and percutaneous intervention. Nineteen patients underwent PCI before surgery, and 38 patient underwent PCI after surgery. No in-hospital mortality occurred. The mean ± SD ICU stay was 1 ± 1 days and the mean ± SD hospital stay was 5 ± 2 days. Only 13.3% of the patients required a blood transfusion. Six-month angiographic follow-up has been performed in the 95 patients, and it demonstrated a left internal thoracic artery anastomotic patency of 97.9% and stent patency of 92.6%. A total of 77.8 ± 41.4-month clinical follow-up demonstrated 95.1% survival, 92.6% freedom from angina, and 90.7% freedom from any form of coronary revascularization. Conclusions: Hybrid coronary revascularization seems to be a promising and safe revascularization strategy. It provides selected patients with an alternative, functionally complete revascularization with minimal surgical trauma and good long-term clinical outcomes.